2021
DOI: 10.3390/ma14185433
|View full text |Cite
|
Sign up to set email alerts
|

A New Magnesium Phosphate Cement Based on Renewable Oyster Shell Powder: Flexural Properties at Different Curing Times

Abstract: Magnesium phosphate cement (MPC), a new type of inorganic cementitious material, is favored in engineering and construction because of its fast setting speed and high bonding strength, but is limited in practical application due to its high production cost and excessive release of hydration heat. Relevant research has investigated the application of discarded oyster shell powder (OSP) replacing cement mortar and has reported certain improvements to its performance. Consequently, focusing on discovering more ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…That is, an excessively high inclusion of WOSP can disrupt its intended role, leading to a reduction in strength. The absence of WOSP leads to denser microstructures, which is in line with previous findings [62,63]. Overall, it can be concluded that a high WOSP replacement ratio can negatively influence strength development owing to reduced reactivity.…”
Section: Effect Of Wosp Replacement Ratio On the Strength And Microst...supporting
confidence: 91%
“…That is, an excessively high inclusion of WOSP can disrupt its intended role, leading to a reduction in strength. The absence of WOSP leads to denser microstructures, which is in line with previous findings [62,63]. Overall, it can be concluded that a high WOSP replacement ratio can negatively influence strength development owing to reduced reactivity.…”
Section: Effect Of Wosp Replacement Ratio On the Strength And Microst...supporting
confidence: 91%
“…According to numerous studies, the properties of cement are largely affected by several parameters: the molar ratio of magnesium to phosphate (M/P), the reactivity of magnesia, the amount of added water [ 3 ], the use of setting retarders, and the initial concentration of phosphate. This type of cement has attracted the widest interest, referring to its outstanding properties such as fast setting time, adhesive properties, low permeability, accelerated resistance development, excellent bonding with almost any clean and dry surface, high strength at an early stage, fast hydration process, fire-resistance properties, lower drying shrinkage [ 4 ], great volume stability, strong bonding force, long durability, and high heat and temperature resistance, and the MPC presents a special environmentally friendly adaptability [ 5 ]. Relying upon these properties, cement displays a wide range of applications such as rapid-repair materials for deteriorated bridge decks, highways, and airport runways; the rehabilitation of damaged civil structures; biomedical materials design; bone restoration; the stabilization of toxic matters and nuclear wastes; and the solidification and stabilization of radioactive wastes and heavy metallic ions.…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale research was carried out regarding the reuse of discarded shells to replace conventional materials [7]. In the civil construction industry, studies of the incorporation of oyster shell wastes can be found for concrete [24][25][26][27], brick [28,29], hot-mix asphalt [30], artificial stone [31], soil mixing and drainage layers [32,33], magnesium phosphate cement [34], and residential finish [35]. This range of research demonstrates the great potential of using shell residues in different contexts in the field of civil construction, which motivates the present study.…”
Section: Introductionmentioning
confidence: 99%